Computer simulations of the stainless steel composition changes induced by neutron based nuclear reactions - Rudychev, Y.V.; Khazhmuradov, M.A.; Prokhorets, S.I.; Fedorchenko, D.V. (Вопросы атомной науки и техники, 2009)
Problem of construction material composition changes induced by neutron fluxes of nuclear reactor VVER-1000 as a result of a nuclear reaction and associated activation processes was considered. The special methodic to simulate this processes using computer simulation methods was developed. Stainless steel H18N10T composition changes during a long irradiation time was simulated.